DIFFERENT BRANCHES OF GLOBAL ACCOUNTING AND ACCOUNTANTS RESPONSIBILITIES: A STUDY IN BRIEF SPECTRUM - Abedin, Rejaul (Accounting Department,, 2018)
Modern organizations are increasingly becoming more complex whether it is sole proprietorships, partnerships or Limited Liability Companies (LLC) (and in many cases global) thereby engendering the need for complete, transparent, reliable and accurate information that can be accessed quickly by the assistance of different branches of global professional accountants such as Certified Professional Accountant, Chartered Accountant, Certified Public Accountant, Management Accountant, Cost Accountant, Financial Accountant, General Accountant, Auditor, Tax Accountant, CA, CPA, CMA, CIMA, CFA, CFO, ICPA and so on. Internationally most large business organizations are well organized by a broad and disparate set of shareholders. These shareholders require the information i.e. quantitative (financial) and qualitative (non-financial) relating to their various organizations in order to make ongoing decisions through financially like dividend or non-financially or strategic decisions – which can range from deciding to invest more and hold more shares, sell off part or all of their holdings, take critical decision on the management and boards of the financial institutions and banks etc. Besides, other stakeholders need the information to make decisions relating to lending, taxation, employee benefits and remuneration. It is essential that the quality of decisions that investors can make is largely dependent on the reliable and quality of information available to them. However, one thing that is common to all organizations is that the accountant plays a pivotal role towards the successful achievement of their strategic objectives by ensuring that the critical ingredient required for decision making is prepared and presented in the required format.